Evaluation of the Implementation of Payments for Building Construction Projects using APBD Funds According to Contract Law - Agil Resfani Mardhiyah; Benny Hidayat; Taufika Ophiyandri (CIVED, 2025)
Late payment is a common problem that often occurs in construction projects and can hinder project completion. Previous studies have stated that factors that influence late payment include the financial condition of the project owner and poor business management as well as delays in payment by the project owner and others. Previous studies only discussed the factors that cause late payment. This study aims to identify factors that influence late payment and find solutions to overcome them. The research method used is qualitative with in-depth interviews with parties involved in construction projects, such as PPK and Contractors. Data were processed using interview transcripts and analyzed with thematic analysis to identify emerging patterns or themes. The results of the study indicate that the procedures for implementing payments have been regulated in contracts and related regulations. Factors that cause late payment include poor communication, administrative negligence, empty regional treasury, and unclear regulations. The proposed solution is to conduct training for HR and hold daily or weekly meetings involving all related parties. This research is expected to contribute to increasing payment efficiency in construction projects. This study has limitations, namely the lack of quantitative data and local context, limited samples, focusing on internal factors.